2015
DOI: 10.1111/2041-210x.12341
|View full text |Cite
|
Sign up to set email alerts
|

Troubleshooting the potential pitfalls of cross‐fostering

Abstract: Summary1. Cross-fostering is the transfer of offspring between their natal environment and a new social environment. This method allows researchers to disentangle the genetic and interacting environmental effects that influence phenotypes, and is popular in both wild and laboratory studies. Here, we discuss three factors that might bias cross-fostering and influence ecological and evolutionary conclusions if not accommodated. 2. First, cross-fostering tends to be spatially and temporally non-random because het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…Therefore we have reason to be equally confident about the accuracy of our estimates of LRS. iv) Finally, a large proportion of broods was cross-fostered systematically from 2000 onwards (14). These data allow us to differentiate among the effects of the genetic parents, the effects of early social environment, and the effects of parent-offspring interactions after hatching (44).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore we have reason to be equally confident about the accuracy of our estimates of LRS. iv) Finally, a large proportion of broods was cross-fostered systematically from 2000 onwards (14). These data allow us to differentiate among the effects of the genetic parents, the effects of early social environment, and the effects of parent-offspring interactions after hatching (44).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, if it were caused by a transgenerational, epigenetically inherited effect, then we would expect the age of the foster parent to have no effect on the annual number of recruits of the focal bird. Therefore we used a dataset of focal birds that had been cross-fostered (14) and for which the age of the cross-fostered parents was known (n = 453 foster mothers, n = 385 foster fathers). We ran two analyses, one for each parental sex, including both the foster and genetic parents' ages to distinguish between the effects of both.…”
Section: Parental Agementioning
confidence: 99%
See 1 more Smart Citation
“…This population has extremely low rates of immigration and emigration, and high resighting probabilities (Simons et al ., ), so the survey has a very limited bias. A large proportion of nestlings were cross‐fostered on the day after hatching (Winney et al ., ). This manipulation increases our power to separate premanipulation maternal effects from additive genetic and post‐manipulation environmental (social brood) effects (Kruuk & Hadfield, ).…”
Section: Methodsmentioning
confidence: 97%
“…In contrast, Winney et al. () showed that in house sparrows ( Passer domesticus ), cross‐fostered offspring had higher survival, but attributed this to methodological problems. The partial cross‐fostering design does not allow the consequences of parent–offspring coadaptation on parental fitness to be measured, as all parents rear a mix of related and unrelated offspring.…”
mentioning
confidence: 96%